Selectivity engineering of Meerwein arylation in a continuous flow reactor: a modelling approach - Shukla, Chinmay A.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2020)
This paper presents a methodology for selectivity engineering of Meerwein arylation in a flow reactor. The reaction was optimized in batch mode and reaction kinetics were obtained over a range of temperatures and catalyst concentrations. A lumped kinetic model was formulated and the parameters were estimated using nonlinear regression. Furthermore, telescopic flow synthesis for Meerwein arylation via in situ diazonium salt generation and coupling was demonstrated. A non-isothermal model was developed and experimentally validated. The effect of initial concentration and inlet temperature on the yield of the desired product was estimated for various catalyst concentrations. The results from the simulations in terms of nondimensional numbers were used to find suitable operating conditions for Meerwein arylation.

Scalable, sustainable and catalyst-free continuous flow ozonolysis of fatty acids - Atapalkar, Ranjit S.; Athawale, Paresh R.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Green Chemistry, 2021)
A simple and efficient catalyst-free protocol for continuous flow synthesis of azelaic acid is developed from the renewable feedstock oleic acid. An ozone and oxygen mixture was used as the reagent for oxidative cleavage of double bond without using any metal catalyst or terminal oxidant. The target product was scaled up to more than 100 g with 86% yield in a white powder form. Complete recycling and reuse of the solvent were established making it a green method. The approach is significantly energy efficient and also has a very small chemical footprint. The methodology has been successfully tested with four fatty acids making it a versatile platform that gives value addition from renewable resources.